2014
DOI: 10.5194/amt-7-731-2014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of FORMOSAT-3/COSMIC level 2 "atmPrf" global temperature data in the stratosphere

Abstract: Abstract. GPS radio occultations by Formosa Satellite mission-3/Constellation Observing System for Meteorology, Ionosphere, and Climate (FORMOSAT-3/COSMIC) provide bending angle profiles, which are further processed to give profiles of temperature and water vapour in the lower atmosphere and electron density in the upper atmosphere. The level 2 "atmPrf" (atmospheric profile) product of version 2010.2640 gives temperature from surface to 0.2 hPa (∼ 60 km). This is a dry temperature data product that does not in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Higher concentrations or gradients of water vapor near the tropopause are not an error source this way. The "wetPrf" and dry temperature "atmPrf" profiles agree extremely well in a validation study by Das and Pan [2014], with absolute zero difference above the 200 hPa level. Less than 1% of the profiles is rejected by a preliminary quality control.…”
Section: Methodssupporting
confidence: 53%
“…Higher concentrations or gradients of water vapor near the tropopause are not an error source this way. The "wetPrf" and dry temperature "atmPrf" profiles agree extremely well in a validation study by Das and Pan [2014], with absolute zero difference above the 200 hPa level. Less than 1% of the profiles is rejected by a preliminary quality control.…”
Section: Methodssupporting
confidence: 53%
“…In this paper, we use GPS wet profile (wetPrf) retrieved at 100 m vertical resolution using a one-dimensional variational technique based on ECMWF analysis. The wetPrf and GPS atmospheric profile (atmPrf, derived assuming no water vapor in the air) temperatures are essentially the same at 200-10 hPa, but at altitudes lower than the 200 hPa level the errors in atmPrf could be as high as ∼ 3 K due to neglect of water vapor (Das and Pan, 2014). Despite being retrieved at 100 m resolution, the actual vertical resolution ranges from 0.5 km in the lower troposphere to ∼ 1 km in the middle atmosphere (Kursinski et al, 1997).…”
Section: Gps Temperaturementioning
confidence: 96%
“…Compared to the global radiosonde data, a small bias of −0.09 K ± 1.72 K was observed in the height range from 925 to 10 hPa. On the other hand, Das and Pan (2014) reported that the temperature differences between CDAAC wetPrf (wet) and atmPrf (dry) version 2010.2640 are nearly zero from 200 to 10 hPa. Although the dry temperature retrieval deviates from the real temperature in a moist atmosphere (Scherllin-Pirscher et al 2011), the atmPrf version 2010.2640 is not affected by water vapor above about 10 km.…”
Section: Cosmic Gps-romentioning
confidence: 99%